2014
DOI: 10.1177/0748730414544741
|View full text |Cite
|
Sign up to set email alerts
|

USP2 Regulates the Intracellular Localization of PER1 and Circadian Gene Expression

Abstract: Endogenous 24-h rhythms in physiology are driven by a network of circadian clocks located in most tissues. The molecular clock mechanism is based on feedback loops involving clock genes and their protein products. Posttranslational modifications, including ubiquitination, are important for regulating the clock feedback mechanism. Recently, we showed that the deubiquitinating enzyme ubiquitin-specific peptidase 2 (USP2) associates with clock proteins and deubiquitinates PERIOD1 (PER1) but does not affect its ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 62 publications
(91 reference statements)
1
26
0
Order By: Relevance
“…We further found that USP2a ( S1 Table ), but neither USP30 nor USP52, bound to pY701-STAT1 ( S4A Fig ). The USP2 family includes two major isoforms, USP2a (69 KDa) and USP2b (45 KDa) [ 27 , 28 , 29 ]. To further investigate the role of USP2, we turned to a USP2 specific antibody, which can recognize human but not mouse USP2a and USP2b.…”
Section: Resultsmentioning
confidence: 99%
“…We further found that USP2a ( S1 Table ), but neither USP30 nor USP52, bound to pY701-STAT1 ( S4A Fig ). The USP2 family includes two major isoforms, USP2a (69 KDa) and USP2b (45 KDa) [ 27 , 28 , 29 ]. To further investigate the role of USP2, we turned to a USP2 specific antibody, which can recognize human but not mouse USP2a and USP2b.…”
Section: Resultsmentioning
confidence: 99%
“…A 50 ng aliquot of total RNA was reverse-transcribed and amplified with a One-Step SYBR reverse transcription PCR (RT-PCR) kit (TaKaRa Bio Inc, Shiga, Japan) in the PikoReal Real-Time PCR System (Thermo Fisher Scientific, Inc., Kanagawa, Japan). The specific primer pairs were designed based on published data for 18S ribosomal RNA (rRNA) , Ocln , Cldn3 , and E4bp4 genes 40 41 42 . The primer sequences are described in Supplementary Table.…”
Section: Methodsmentioning
confidence: 99%
“…Among the proteins that USP2 (ubiquitin specific protease 2) deubiquitinates is the circadian clock protein PER1. In doing so it regulates the entry of PER1 into the nucleus [ 88 ]. Since Usp2 expression was up-regulated at night in the Hartley dataset, based on the findings of Yang et al [ 88 ] we would expect an increased nuclear accumulation of Usp2 at night in the rat pineal gland.…”
Section: Resultsmentioning
confidence: 99%
“…In doing so it regulates the entry of PER1 into the nucleus [ 88 ]. Since Usp2 expression was up-regulated at night in the Hartley dataset, based on the findings of Yang et al [ 88 ] we would expect an increased nuclear accumulation of Usp2 at night in the rat pineal gland. A role for Usp2 in regulation of circadian rhythms and Per1 was previously reported by this group based on observations on tissues of Usp2 knockout mice [ 89 ].…”
Section: Resultsmentioning
confidence: 99%